An exploration of occupational personality traits and communicative competence in New Zealand leaders and non-leaders : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Psychology, Massey University, Palmerston North, New Zealand. EMBARGOED until further notice. - Schischka, Caroline E (Massey University, 2015)
The thesis reports New Zealand empirical research on leadership and its antecedents in terms of occupation-relevant personality traits and communicative competence. Objectives of the project were to: (i) explore the demographic differences in personality traits and communicative competence; (ii) investigate the difference between leaders and non-leaders in terms of personality and communicative competence; (iii) examine whether patterns of relationships among personality and communicative competence variables differ between leaders and non-leaders. These objectives govern research that aims at alleviating the current scarceness in New Zealand organisational psychology literature regarding personality traits and communicative competence of leaders. In a cross-sectional, correlational design, the Business Attitudes Questionnaire was used as a personality inventory, and the Political Skill Inventory as a measure of particular segments of communicative competence. Findings showed that males scored higher on Openness than females; age and work experience were both significantly positively related with Extraversion. When comparing leaders versus non-leaders, leaders scored higher on Emotional Stability, Extraversion, Professionalism and Networking Ability than non-leaders. The personality traits Extraversion, Altruism and Conscientiousness were significantly positively related to the four aspects of Ferris' "political skill" as an aspect of communicative competence. There were systematic differences found between leaders and non-leaders regarding the correlational pattern between personality and communicative competence. Relationships between Altruism, Conscientiousness, and Openness, on one hand, and all four aspects of "political skill", on the other, were stronger for leaders than non-leaders. A few relationships – such as those between Extraversion, Emotional Stability and Professionalism, on one hand, and some aspects of "political skill" – were higher among non-leaders. These findings are discussed in terms of their convergence with and divergence from the existing literature. Limitations of the present study are critically scrutinised, followed by extrapolations for future research. Overall, the research identified a clear need for further examination into psychological predictors and concomitants of leadership such as personality and communicative competence in the New Zealand working environment.
Embargoed until further notice
Keywords: Leadership; Communicative competence; Personality; Personality traits; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Psychology